Neonatal multisystem inflammatory syndrome associated with prenatal maternal SARS-CoV-2 exposure: a case series - Tambekar, Harish J.; Ashtekar, Satish D.; Mirgunde, Shishir P.; Khot, Swati; Mane, Shrikant (International Journal of Contemporary Pediatrics, 2022)
Multisystem inflammatory syndrome (MIS-C) in children (MIS-C) associated with severe acute respiratory syndrome coronavirus-2 (SARS-CoV2) is well recognised in children, however, rarely reported in newborns. It usually presents as fever and multiorgan involvement, with blood investigations showing increased inflammatory markers weeks after exposure to SARS-CoV-2. Unlike older children, the mechanism is unique in neonates as COVID-19 infection and the subsequent inflammatory reaction leading to MIS-C occur in two different individuals. We reviewed the perinatal history, clinical features, and outcomes of 3 neonates with features consistent with MIS-N related to maternal SARS-CoV-2, from August 2021 to December 2021. Anti-SARS-CoV-2 IgG and IgM antibodies were tested in all neonates. Clinical picture comprised multiorgan dysfunction (gastrointestinal, cardiorespiratory, haematological and dermatological), positive inflammatory markers, high ferritin and high D-dimer levels, elevated Cardiac enzymes. Blood cultures were sterile. Positive anti-SARS-CoV-2 IgG in both the mother and the infant, along with epidemiological evidence of maternal contact with COVID-19, clinched the diagnosis of MIS-C. Immunomodulatory drugs (intravenous immunoglobulin and systemic steroids) were administered. Multisystem inflammatory syndrome should be considered as a differential diagnosis in all critically ill neonates, particularly with maternal history of COVID-19 infection or epidemiological contact. This neonatal presentation is the reflection of fetal inflammatory response syndrome associated with maternal SARS-CoV-2 infection. Having no fever throughout the course of illness, in some neonates, suggests that neonates respond differently compared with children.